2015
DOI: 10.1002/jbm.a.35446
|View full text |Cite
|
Sign up to set email alerts
|

Albuminated PLGA nanoparticles containing bevacizumab intended for ocular neovascularization treatment

Abstract: Bevacizumab, an anti-VEGF antibody, has demonstrated trustworthy effects in treatment of retinal and choroidal neovascularization that both are crucial sight threatening conditions. However, the weak point is the short half-life of the drug in vitreous which necessitates frequent intravitreal injections. Accordingly employing controlled-release drug delivery systems such as polymeric nanoparticles (NPs) has been suggested. In this study albuminated-PLGA-NPs containing bevacizumab were prepared and studied inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
60
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(65 citation statements)
references
References 35 publications
(44 reference statements)
3
60
0
Order By: Relevance
“…One possible strategy to overcome these problems resides in the antibody encapsulation into biodegradable and biocompatible polymers creating a tailorable nanosystem. [15][16][17] In this way, the loaded antibody is protected from degradation and from interaction with the immune system and can be released in a controlled manner. Poly(lactic-co-glycolic) acid (PLGA) is an excellent candidate, as it has been approved by FDA for human use because of its biodegradability and low systemic toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…One possible strategy to overcome these problems resides in the antibody encapsulation into biodegradable and biocompatible polymers creating a tailorable nanosystem. [15][16][17] In this way, the loaded antibody is protected from degradation and from interaction with the immune system and can be released in a controlled manner. Poly(lactic-co-glycolic) acid (PLGA) is an excellent candidate, as it has been approved by FDA for human use because of its biodegradability and low systemic toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Many of the studies have demonstrated that sustained release for anti-VEGF molecules can be achieved for more than 1 month in in vitro and in vivo models [58,[60][61][62][63][64]. However, data regarding the bioactivity exerted by the anti-VEGF loaded particles in reducing retinal neovascularisation in vivo remains limited [58].…”
Section: Nps and Microparticles (Mps)mentioning
confidence: 99%
“…They found that the vitreous concentration of bevacizumab was sustained for about 8 weeks at values greater than 500 ng mL −1 and that the nanoparticles presented a drug vitreous medium retention time (MRT) 3.3 times higher than the control. In addition, it was confirmed the nanoparticles persistence in ocular tissues for 56 days (Varshochian et al, 2013(Varshochian et al, , 2015.…”
Section: Eye Diseasesmentioning
confidence: 60%